The faculty lounge : a novel [large type] - Mathieu, Jennifer (Thorndike Press large print top shelf., 2024)
"It all starts when an elderly substitute teacher at Baldwin High School is found dead in the faculty lounge. After a bit of a stir, life quickly returns to normal--it's not like it's the worst (or even most interesting) thing that has happened within the building's walls. But when, a week later, the spontaneous scattering of his ashes on the school grounds catches the attention of some busybody parents, it sets in motion a year that can only be described as wild, bizarre, tragic, mundane, beautiful, and humorous all at once. In the midst of the ensuing hysteria and threats of disciplinary action, the novel peeks into the lives of the implicated adults who, it turns out, actually have first names and continue to exist when the school day is done. We meet: a former punk band front man, now a middle-aged principal who must battle it out with the school board to keep his job; a no-nonsense school nurse willing to break the rules, despite the close watch on their campus, when a student arrives at her office with a dilemma; and a disgruntled English instructor who finds himself embroiled in even more controversy when he misfires a snarky email. Oh, and there's also a teacher make-out session in a supply closet during a lockdown. As these people continue to manage the messiness of this school year, there is the looming threat of what will become of their beloved Baldwin High. Ultimately, at the heart of this unconventional workplace novel is a story of the power of human connection and of the joy of finding purpose in what it is we do every day." -- Provided by the publisher.